Insulin-Related Lipohypertrophy: Lipogenic Action or Tissue Trauma? - Barola, Anjana; Tiwari, Pramil; Bhansali, Anil; Grover, Sandeep; Dayal, Devi (Frontiers in Endocrinology, 2018)
Lipohypertrophy has been suggested as an outcome of lipogenic action of insulin and/or injection-related tissue trauma. In a cross-sectional study, we evaluated the predictors of lipohypertrophy in 372 type 1 diabetes patients (mean age 17.1 years) receiving subcutaneous insulin with pen and/or syringes for ≥3 months. On examining injection sites with inspection and palpation technique, 62.1% patients demonstrated lipohypertrophy. Univariate analysis showed that age, duration of diabetes, socioeconomic status, injection administrator, needle reuse, total daily dose (TDD) of insulin/kg bodyweight, and number of injection sites did not predict lipohypertrophy (p>0.05). Notably, the mean needle reuse was comparable in patients with or without lipohypertrophy (8.1 vs 7.2, p=0.534). In multivariate logistic regression, gender, HbA1c, TDD, injection devices, and needle length also lost its significance. Further, injections over smaller area (≤8.5x5.5cm) and non-rotation of sites were found to be strongest independent predictor of lipohypertrophy (p<.0005 for both) with increased odds of 23.2 (95% CI 9.1-59.2) and 6.3 (95% CI 3.4-11.9) times, respectively. Being underweight was also a significant independent predictor (odds ratio [OR] 13.0 [95% CI 2.2-75.2], p=0.004). Compared to rapid plus long-acting analogues, regular insulin plus long-acting analogues and conventional premixed insulin users had 3.2 (95% CI 1.5-6.8, p=0.003) and 4.6 (95% CI 1.4-15.7, p=0.014) fold higher risk of lipohypertrophy (mean injection frequency 4.01 vs 4.01 vs 2.09, respectively). Sub-group analysis showed that lipohypertrophy was 79% less likely in patients with multiple daily injections (≥4) than twice-daily regimen (unadjusted OR 0.21, p<0.0005). Moreover, lipohypertrophy was reduced to half with bolus doses of rapid-acting insulin analogues than the regular insulin (p=0.003), even though mean injection frequency was comparable (4.01 vs 3.93, p=0.229). This difference was statistically insignificant for basal doses with NPH or long-acting analogues (p=0.069). Therefore, injection area, rotation, BMI, and insulin regimen are the best predictors of lipohypertrophy and together could correctly identify lipohypertrophy status in 84.4% patients with excellent discrimination capability (AUC=0.906, p<0.0005). In conclusion, findings of our study suggest that delivering rapidly absorbed insulin analogues over large injection area along with greater split of total daily doses reduce insulin-induced lipogenesis and outplay tissue trauma added through frequent injections.